PENGARUH MOTIVASI DAN PERSEPSI TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR YAMAHA - Ardian Reza Yudistira (2013)
Motivation is the psychological power that shape human behavior is largely unconscious and that one can not fully understand his motivation. Perception is the process by which a person choosing, organizing and interpreting information inputs to create a meaningful picture of the world the same. The purchase decision is the stage when consumers decide whether to buy or not. If it is considered that the decision is to buy, then the buyer will encounter a series of decisions on the type of product, the form of products, brands, sellers, quantity, time of purchase, and how to pay. The purpose of this study was to determine and analyze the extent to which the fit between Motivation and Perceptions of Buying Decision yamaha motorcycle. This study uses primary data collected from respondents (Yamaha Motor bike users). The study of 100 respondents visitors corals motorcycle dealer Lebak Bulus using linear regression analysis method. This technique identifies to know where the relationship between the dependent and independent variables are each independent variable associated positively or negatively and to predict the value of the dependent variable when the independent variable value has increased or decreased.